(untitled) (Journal of Accounting and Financial Studies ( JAFS ), 2022)
Islamic banks are distinguished by providing banking activities that are unique in providing them from the rest of the other types of banks, and these activities are a group of banking services provided by the bank to its customers, whether these banking activities are tangible or intangible. At the same time, it is a source of bank profits, as Islamic banks impose a percentage of Islamic Murabaha on those banking activities , However, these banks have developed new services that they provide with the funds of the Central Bank initiative launched at the beginning of (2016) due to the economic conditions that befell the country due to the (financial security) crisis that the country faced in 2014. To put forward initiatives, and among these initiatives is the initiative of the (1 trillion) Iraqi dinars, which was put forward by private commercial and Islamic banks . The importance of research is highlighted in knowing the positive or negative impact that the Central Bank of Iraq’s initiative has on the activities offered by Islamic banks (the private sector) and on the activities of these banks. Islamic self-banking , As the research started from a basic assumption based on the success of the Central Bank of Iraq in its initiatives to support small projects, which amounted to (2 trillion) dinars, by positively affecting the operations and activities of private Islamic banks, The research relied on the inductive, deductive and analytical approach in analyzing the annual data of the initiatives submitted by Islamic banks according to the participation of Islamic banks in the research sample, and the research has several achievements, most notably (non-traditional monetary policies are one of the most important tools that central banks resort to at the time of crises , As happened during the Great Depression of 1929-1932 or the global financial crisis of 2008) and to a set of recommendations, the most important of which is (the use of unconventional monetary policy came to confront some financial crises, and since the seed of these crises has sprouted in the environment of the banking system, so it has become It is necessary to study the ways to improve the status of the banking system and develop transparency and safety procedures, as well as setting the necessary controls to prevent practices that are harmful to banking activity.